Constructing a Knowledge Test to Measure the Knowledge Level of Farmers about Climate Change in Arid Ecosystem of India - Sarkar, Sujit; Padaria, R. N.; Vijayaragavan, K.; Pathak, Himanshu; Bhowmik, Arpan; Kumar, Pramod; Jha, G. K. (International Journal of Bio-resource and Stress Management, 2023)
Climate change has brought widespread misery and economic loss to farming community of India, adversely affecting agriculture, public health, food security, biodiversity and water resources. Climate change is a very complex issue and most of the farmers did not have any clear cut understanding about it. So it is very important to measure the knowledge level of farmers for successful adaptation. The present study is aimed to construct a knowledge test to measure the knowledge level of farmers in India. One pilot study was conducted to develop the test in Lechura village of Uttar Pradesh. The test was developed with reliability score of 0.709 and a sufficient degree of validity. The final study was conducted in Jodhpur and Jaisalmer district of Rajasthan. The study revealed that only 34% farmers knew about climate change and only 31% farmers knew that paddy cultivation also leads to emission of green house gasses. Cumulatively 45% respondents come under low level of knowledge category on climate change. The correlation analysis revealed that different social variables like education (0.800*), perception (0.638*), social participation (0.471*) and psychological variable like attitude (0.815*), value (0.820) and awareness (0.743*) were correlated positively with knowledge score of the respondents. However age (-0.257*), income (-0.003), area (-0.006), pessimism (-0.621*) and stress (-0.451) were correlated negatively. So policy maker should take into consideration these social and psychological dimensions of farmers’ behavior for successful implementation of any adaptation strategy to climate change.